Influential macroeconomic factors of stock price: A study on Dhaka stock exchange - Khandoker, Mohammad Sogir Hossain; Bhuyan, Rafiqul; Ahmad, Khaled (The Economics and Finance Letters, 2025)
This research aims to find out the impacts of macroeconomic factors on the stock market performance of Bangladesh. It has focused on finding out the short-run and long-run impacts of the variables. Call money rate (CMR), foreign borrowing (FB), import payment (IMPMT), and GDP growth rate (GDPGR) variables are used as independent variables, and stock price is used as the dependent variable. Monthly data from 2013 to 2022 are used for the analysis. The augmented distributed lag (ARDL) model is used for analysis. In addition, Granger causality and the error correction in short-run disequilibrium to long-run equilibrium are measured. All the macroeconomic variables except IMPMT at the first lag have an impact on the stock price. CMR has a negative relation with stock price, and all other variables have a positive relation. In the long run, all the variables are also impacting the stock price significantly. Short-run disequilibrium is being equilibrated in the long run by 32.35 percent each month. Granger causality analysis shows that except for FB, the other three variables, i.e., CMR, IMPMT, and GDPGR, have a causal relationship with the stock price in different forms. The research has found significant influential macroeconomic factors of stock price, and by using the findings, policymakers will be able to take appropriate measures.